Influence of substituents on selectivity and efficiency of chiral separations of anions containing single nido-7,8-dicarbaundecaborane cluster with alpha-cyclodextrin - Horáková, Hana; Vespalec, Radim (Journal of chromatography. A, Including electrophoresis and other separation methods, 2007)
n background electrolyte (BGE) with the optimal methanol concentration of 30% (v/v), the ion with -NCS group bonded to a cluster boron atom exhibits the strongest interaction with alpha-cyclodextrin and the highest separation selectivity. Interaction of ions with alkyl or thioalkyl group weakens with the increasing substituent size. The ion with phenyl group exhibits the weakest interaction. Bonding of a group to boron atom weakens the ion interaction with alpha-cyclodextrin. Second substituent further weakens the interaction with alpha-cyclodextrin. Separation efficiency is lower at the presence of alpha-cyclodextrin than at its absence. This separation efficiency loss, amounts up to 90%.
Keywords: borany; financování organizované; alfa-cyklodextriny; Financing, Organized; Boranes; anionty; Anions; alpha-Cyclodextrins; Sensitivity and Specificity; Stereoisomerism; stereoizomerie; senzitivita a specificita